Cognitive and brain reserve in conversion and reversion in patients with mild cognitive impairment over 12 months of follow-up. Issue 10 (25th November 2016) - Osone, Akira; Arai, Reiko; Hakamada, Rina; Shimoda, Kazutaka
ABSTRACT: Introduction : Two reserve hypotheses have been proposed to account for the observed disjunction between the degree of brain pathology and its clinical manifestations. This study investigated whether cognitive reserve (CR), taken here as educational attainment and premorbid IQ, or brain reserve (BR; i.e., brain volume) is associated with progression and regression in patients with mild cognitive impairment (MCI) over a 12-month follow-up. Method : Patients with MCI ( n = 123) were prospectively enrolled. The Mini-Mental State Examination, the Japanese version of the Cognitive subscale of the Alzheimer's Disease Assessment Scale, the Clinical Dementia Rating (CDR), the Frontal Assessment Battery, the Neuropsychiatric Inventory, magnetic resonance imaging (MRI), and quantitative single-photon emission computed tomography were performed at intake and again at 12-month follow-up. Patients were classified into three groups: no change, conversion, and reversion. Conversion was defined as a change in CDR from 0.5 to 1, and reversion as a change from 0.5 to 0. Results : Voxel-based morphometry MRI revealed no significant differences in entorhinal and hippocampal gray matter loss among the groups. Patients with reversion had higher premorbid IQ ( p = .03, ηp 2 = .35) as measured by the Japanese version of the National Adult Reading Test, higher atrophy ratio (hippocampal volume/whole brain volume; p = .04, ηp 2 = .89) at baseline, and better cognitive performance ( p < .001) during the 12-month follow-up than those with conversion did. There were no statistically significant differences among the three groups in terms of years of education. Conclusion : Multinomial logistic regression analysis revealed that higher CR contributed to protecting against cognitive decline during the 12-month follow-up, whereas higher BR at baseline was the strongest predictor for reversion and conversion.